2012
DOI: 10.1007/s00167-012-2119-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of significant glenoid bone defects and associated humeral avulsions of glenohumeral ligament (HAGL) lesions in anterior shoulder instability

Abstract: Therapeutic study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
0
30
1
1
Order By: Relevance
“… 6 , 26 , 30 A failed nonoperative management course, ranging from 1 to 22 months, was the surgical indication in 4 studies 13 , 20 , 22 , 25 comprising 31 patients. Preoperatively, HAGL lesions were confirmed by either magnetic resonance imaging or magnetic resonance arthrogram in 5 studies 1 , 7 , 12 , 22 , 32 for total of 44 total patients. One author 12 reported that 3 of 6 HAGL lesions were missed on magnetic resonance imaging and confirmed intraoperatively.…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 26 , 30 A failed nonoperative management course, ranging from 1 to 22 months, was the surgical indication in 4 studies 13 , 20 , 22 , 25 comprising 31 patients. Preoperatively, HAGL lesions were confirmed by either magnetic resonance imaging or magnetic resonance arthrogram in 5 studies 1 , 7 , 12 , 22 , 32 for total of 44 total patients. One author 12 reported that 3 of 6 HAGL lesions were missed on magnetic resonance imaging and confirmed intraoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…In outcomes studies, the contralateral shoulder is frequently used as a marker of ''normal'' strength and range of motion, particularly in the setting of rotator cuff tears and trauma. [2][3][4][5]9,16,25 To our knowledge, no previous studies have used this as a basis for evaluating recovery of subscapularis strength after shoulder arthroplasty. The primary objective of this study was to determine whether subscapularis strength returns to normal after shoulder arthroplasty by comparison to the normal, contralateral side.…”
mentioning
confidence: 99%
“…The authors reported excellent results in a large series of patients using this technique. 7,8 Biomechanical studies have further quantified the role of capsular closure in this procedure. The procedure is performed with special instrumentation (Mitek) that simplifies the procedure and makes it reproducible and safe.…”
Section: Historical Perspectivementioning
confidence: 99%
“…7 Balg and Boileau 12 have described an Instability Severity Index Score, and a score of 6 or greater necessitates a bone grafting procedure like the ALCS. 7 Balg and Boileau 12 have described an Instability Severity Index Score, and a score of 6 or greater necessitates a bone grafting procedure like the ALCS.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation